Validation of a method for noninvasive prenatal testing for fetal aneuploidies risk and considerations for its introduction in the Public Health System. (19th March 2017) - Gerundino, Francesca; Giachini, Claudia; Contini, Elisa; Benelli, Matteo; Marseglia, Giuseppina; Giuliani, Costanza; Marin, Francesca; Nannetti, Genni; Lisi, Ermanna; Sbernini, Fiammetta; Periti, Enrico; Cordisco, Adalgisa; et al.
Abstract: Objective : The aim of this study was to validate noninvasive prenatal testing (NIPT) for fetal aneuploidies by whole-genome massively parallel sequencing (MPS). Methods : MPS was performed on cell-free DNA (cfDNA) isolated from maternal plasma in two groups: a first set of 186 euploid samples and a second set of 195 samples enriched of aneuploid cases ( n = 69); digital PCR for fetal fraction (FF) assessment was performed on 178/381 samples. Cases with <10 × 10 6 reads ( n = 54) were excluded for downstream data analysis. Follow-up data (invasive testing results or neonatal information) were available for all samples. Performances in terms of specificity/sensitivity and Z-score distributions were evaluated. Results : All positive samples for trisomy 21 (T21) ( n = 43), trisomy 18 (T18) ( n = 6) and trisomy 13 (T13) ( n = 7) were correctly identified (sensitivity: 99.9%); 5 false positive results were reported: 3 for T21 (specificity = 98.9%) and 2 for T13 (specificity = 99.4%). Besides FF, total cfDNA concentration seems another important parameter for MPS, since it influences the number of reads. Conclusions : The overall test accuracy allowed us introducing NIPT for T21, T18 and T13 as a clinical service for pregnant women after 10 + 4 weeks of gestation. Sex chromosome aneuploidy assessment needs further validation due to the limited number of aneuploid cases in this study.